2018
DOI: 10.1080/10641963.2018.1545850
|View full text |Cite
|
Sign up to set email alerts
|

Long-term low salt diet increases blood pressure by activation of the renin-angiotensin and sympathetic nervous systems

Abstract: Background-The aim of this study was to investigate the effect of long-term low salt diet on blood pressure and its underlying mechanisms. Methods-Male Sprague-Dawley (SD) rats were divided into normal salt diet group (0.4%) and low salt diet group (0.04%). Blood pressure was measured with the non-invasive tail-cuff method. The contractile response of isolated mesenteric arteries was measured using a small vessel myograph. The effects on renal function of the intrarenal arterial infusion of candesartan (10 µg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
2
7
0
1
Order By: Relevance
“…We observed that higher Urinary sodium and UIC were proportionately related to high blood pressure. We also observed in another study that salt uptake was directly associated with high blood pressure (14) . Our findings were supported by Surya Bali et al (18) .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We observed that higher Urinary sodium and UIC were proportionately related to high blood pressure. We also observed in another study that salt uptake was directly associated with high blood pressure (14) . Our findings were supported by Surya Bali et al (18) .…”
Section: Discussionsupporting
confidence: 70%
“…But, reduction of salt intake to control hypertension has been opposed by experts involved in Iodine Deficiency Disorder (IDD) (12) . Further, a few studies have demonstrated a positive correlation between low salt intake and higher risk of hypertension or cardiovascular events (14,14) . Moreover, prolonged practice of low salt increases blood pressure through activation of the renin-angiotensin and sympathetic nervous systems (13) .…”
Section: Introductionmentioning
confidence: 99%
“…A previous prospective study in 17 countries reported that mortality and cardiovascular events are greater on both a high sodium excretion, as well as on a low sodium excretion [ 25 ], and some populations demonstrate an increase in blood pressure on a low sodium diet and are considered to be inverse salt sensitive [ 26 ]. Therefore, some patients with diabetes who are inverse salt-sensitive and follow national federal guidelines for lower sodium consumption may have elevated blood pressure by activation of renin-aldosterone and sympathetic nerve systems [ 27 ], leading to the development of vascular complications. Second, elderly type 2 diabetes patients with low sodium intake have lower intakes of food groups and nutrition that were reported to be associated with reduced risk of diabetic complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the reliability of the measurements, rats were trained for one week to acclimatize them to the process of measurement. Blood pressure was measured using a computerized noninvasive tail-cuff manometry system (MODEL MK-2000; Muromachi Kikai Co. Ltd, Tokyo, Japan) in conscious rats between 2 and 5 PM every day, as reported in our previous studies [17,18].…”
Section: Blood Pressure Measurement and Urine/blood Analysismentioning
confidence: 99%
“…The protein expressions of angiotensin II type 1 receptor (AT 1 R), G-protein-coupled receptor kinase type 4 (GRK4), GAPDH and tubulin were determined by immunoblotting, as reported in our previous studies [14,[16][17][18]. In brief, equal amounts of total extracted proteins (100 μg) were separated on SDS-PAGE and were transferred onto nitrocellulose membranes (Amersham Life Science, Arlington, TX).…”
Section: Immunoblottingmentioning
confidence: 99%